Does board gender diversity increase dividend payouts? Analysis of global evidence - Ye, Dezhu; Deng, Jie; Liu, Yi; Szewczyk, Samuel H.; Chen, Xiao (Journal of Corporate Finance, 2019)
Employing 63,464 firm-year observations of 8876 companies in 22 countries from 2000 to 2013, we conduct a series of multiple regression analyses that reveal a significantly positive relationship between board gender diversity and dividend payouts. The empirical results confirm that board gender diversity facilitates corporate governance and consequently promotes dividend payouts. We also show that a good institutional environment may weaken the effect of board gender diversity on dividend payouts. Institutional ownership is positively associated with board gender diversity and that corporate dividend payouts increase when female senior executives have shareholdings. The findings of our analysis are robust after controlling for potential endogeneity concerns.